Overexpression of the Brassica rapa transcription factor WRKY12 results in reduced soft rot symptoms caused by Pectobacterium carotovorum in Arabidopsis and Chinese cabbage. (19th February 2014) - Kim, H. S.; Park, Y. H.; Nam, H.; Lee, Y. M.; Song, K.; Choi, C.; Ahn, I.; Park, S. R.; Lee, Y. H.; Hwang, D. J.; van Wees, S.
Abstract Chinese cabbage (Brassica rapa L. ssp. pekinensis), an important vegetable crop, can succumb to diseases such as bacterial soft rot, resulting in significant loss of crop productivity and quality. Pectobacterium carotovorum ssp. carotovorum (Pcc) causes soft rot disease in various plants, including Chinese cabbage. To overcome crop loss caused by bacterial soft rot, a gene from Chinese cabbage was isolated and characterised in this study. We isolated the BrWRKY12 gene from Chinese cabbage, which is a group II member of the WRKY transcription factor superfamily. The 645‐bp coding sequence of BrWRKY12 translates to a protein with a molecular mass of approximately 24.4 kDa, and BrWRKY12 was exclusively localised in the nucleus. Transcripts of BrWRKY12 were induced by Pcc infection in Brassica. Heterologous expression of BrWRKY12 resulted in reduced susceptibility to Pcc but not to Pseudomonas syringae pv. tomato in Arabidopsis. Defence‐associated genes, such as AtPDF1.2 and AtPGIP2, were constitutively expressed in transgenic lines overexpressing BrWRKY12. The expression of AtWKRY12, which is the closest orthologue of BrWRKY12, was down‐regulated by Pcc in Arabidopsis. However, the Atwrky12‐2 mutants did not show any difference in response to Pcc, pointing to a difference in function of WRKY12 in Brassica and Arabidopsis. Furthermore, BrWRKY12 in Chinese cabbage also exhibited enhanced resistance to bacterial soft rot and increased the expression of defence‐associated genes. In summary, BrWRKY12 confers enhanced resistance to Pcc through transcriptional activation of defence‐related genes.